CALCULATION OF DEFORMATION FORCE AT PLASTIC FORMING OF FLANGE IN THE TUBE SLUG - L. A. Isaevich; M. I. Sidorenko; V. A. Gurinovich (Литьë и металлургия, 2007)
The methods of calculation of straining force at plastic shaping in tube slug with predictable size of surface of bridge from the tube wall to flange are given.